Formation of electrically conducting, transparent films using silver nanoparticles connected by carbon nanotubes - Hwang, Sunna; Noh, Sun Young; Kim, Heesuk; Park, Min; Lee, Hyunjung (ELSEVIER SCIENCE SA, 2014)
To achieve both optical transparency and electrical conductivity simultaneously, we fabricated a singlewalled carbon nanotube (SWNT)/silver fiber-based transparent conductive film using silver fibers produced by the electrospinning method. Electrospun silver fibers provided a segregated structure with the silver nanoparticles within the fibrous microstructures as a framework. Additional deposition of SWNT/poly(3,4-ethylenedioxythiophene) doped with poly( styrenesulfonate) (PEDOT: PSS) layers resulted in a remarkable decrease in the surface resistance from very high value (>3000 k Omega/sq) for the films of electrospun silver fibers, without affecting the optical transmittance at 550 nm. The surface resistance of the SWNT/silver film after the deposition of three layers decreased to 17 Omega/sq with 80% transmittance. Successive depositions of SWNT/PEDOT:PSS layers reduced the surface resistance to 2 Omega/sq without severe loss in optical transmittance (ca. 65%). The transparent conductive films exhibited a performance comparable to that of commercial indium tin oxide films. The individual silver nanoparticles within the electrospun fibers on the substrate were interconnected with SWNTs, which resulted in the efficient activation of a conductive network by bridging the gaps among separate silver nanoparticles. Such a construction of microscopically conductive networks with the minimum use of electrically conductive nanomaterials produced superior electrical conductivity, while maintaining the optical transparency. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: THIN-FILMS; COMPOSITE FILMS; NANOFIBERS; NETWORKS; PEDOT; PERCOLATION; MORPHOLOGY; EFFICIENCY; UNIFORM; MESH